Two new Wittmackia species (Bromeliaceae: Bromelioideae) from Bahia, Brazil - Leme, Elton M. C.; de Souza, Everton Hilo; Aona, Lidyanne Y. S.; Souza, Fernanda V. D. (Phytotaxa, 2023)
The authors describe and illustrate two new species of Wittmackia, W. conduruensis and W. guedesiae. The species are endemic to the state of Bahia with a restricted geographical range, being considered critically endangered (CR) mainly due to habitat fragmentation and illegal extractivism, specifically for regional and international trade. We also present the phenology and compare their morphology with related species.